2012
DOI: 10.1111/ejn.12069
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the neural basis of motor plasticity induced by theta burst stimulation from TMSEEG

Abstract: Transcranial magnetic stimulation (TMS) is a useful tool to induce and measure plasticity in the human brain. However, the cortical effects are generally indirectly evaluated with motor-evoked potentials (MEPs) reflective of modulation of cortico-spinal excitability. In this study, we aim to provide direct measures of cortical plasticity by combining TMS with electroencephalography (EEG). Continuous theta-burst stimulation (cTBS) was applied over the primary motor cortex (M1) of young healthy adults; and we me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 39 publications
6
63
2
Order By: Relevance
“…For example, Vernet et al (2013) have shown that the effects of theta-burst stimulation effects waver over time, indicating that additional factors, such as fluctuations in attention, emotional state and arousal, interact with the TMS-induced changes on cortical excitability levels over time (Schutter et al, 2001;Vernet et al, 2013Vernet et al, , 2014Monte-Silva et al, 2009). Such oscillating patterns are also seen in some PAS studies (Grundey et al, 2012a;Kuo et al, 2007;Nitsche et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Vernet et al (2013) have shown that the effects of theta-burst stimulation effects waver over time, indicating that additional factors, such as fluctuations in attention, emotional state and arousal, interact with the TMS-induced changes on cortical excitability levels over time (Schutter et al, 2001;Vernet et al, 2013Vernet et al, , 2014Monte-Silva et al, 2009). Such oscillating patterns are also seen in some PAS studies (Grundey et al, 2012a;Kuo et al, 2007;Nitsche et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Studies sometimes make such implicit assumptions, but the field is lacking a fundamental insight to accept or modify such assumptions. Encouraging advances have been made on this end for TMS (Thut & Miniussi, 2009;Thut & Pascual-Leone, 2009;Vernet et al, 2013), transcranial alternating current stimulation (tACS; Fröhlich & McCormick, 2010;Herrmann, Rach, Neuling, & Strüber, 2013), and direct brain stimulation (Logothetis et al, 2010;Tolias et al, 2005). For example, Vernet et al(2013) used a combined TMS-EEG approach to evaluate the cortical effects of continuous theta-burst stimulation (cTBS).…”
Section: The Road Ahead: Additional Considerations Regarding Direct Vmentioning
confidence: 99%
“…Future correlation studies between the MEP and the TEP component changes at the single trial level (Mäki and Ilmoniemi, 2010) or between the MEPs and the weighted TEP (Vernet et al, 2013) are necessary to understand the relationship between the tDCS-induced effects on the corticospinal and the cortical excitability and their measures.…”
Section: Correlation Between Corticospinal Excitability and Cortical mentioning
confidence: 99%